If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
(3/4)*y-82+6 = (6/8)*x+24 // - (6/8)*x+24
(3/4)*y-((6/8)*x)-82-24+6 = 0
(-3/4)*x+(3/4)*y-82-24+6 = 0
3/4*y-3/4*x-100 = 0 // - 3/4*y-100
-3/4*x = -(3/4*y-100) // : -3/4
x = (-(3/4*y-100))/(-3/4)
x = -4/3*(100-(3/4*y))
x = -4/3*(100-(3/4*y))
| 3y+3=-4y+1 | | 17+34=38 | | 2x^3+3x^2-54x=0 | | p+4=2p+3 | | 4+g/5=-7 | | x-.3333x=54 | | 3(x-4)+2=23 | | 2q+(-10)=108 | | 3y^2+5y-12=0 | | x-33.33x=54 | | 16y=-112 | | 5x/7+1/14+7/28 | | 16y=11 | | 2x^2+2x-96=0 | | r/3+6=42 | | 2/3x+5/6x+1/2x+10 | | -3(2x+11)=6x+33 | | 1/2(2x+3)+4x=5 | | 120=1.2x | | 2/3(4x-3)=2/5(x-4) | | 4(26-19)= | | y=x+(x*0.2) | | -11=18/5+s/5 | | 585.00+0.13x=850 | | -52-18= | | -2/3x=36 | | (p+12)/2=(8-3p)/4 | | 3y=4(2x-4) | | (-5m^6a^2/4m^-4a^-6)^-1 | | (18n^2-9n+1)/(3n-1) | | x-0.05x=418 | | 1/3(6x-9)=5 |